Molybdenum and tungsten enzymes. - Hille, Russ; Schulzke, Carola; Kirk, Martin L. (RSC metallobiology series ;, 2017)
There has been enormous progress in our understanding of molybdenum and tungsten enzymes and relevant inorganic complexes of molybdenum and tungsten over the past twenty years. This set of three books provides a timely and comprehensive overview of the field and documents the latest research. The first volume in the set focusses on the enzymes themselves, and discusses active sites and substrate channels of relevant proteins. The book begins with an introductory overview of the whole field. Chapters are contributed by world leaders and topics covered include pyranopterin cofactor biosynthesis and incorporation of the mature cofactor into apoprotein. Subsequent volumes cover the bioinorganic chemistry relevant to these enzymes and the full range of spectroscopic and theoretical methods that are used to investigate their physical and electronic structure and function.